PENGARUH JUMLAH UANG BEREDAR DAN SUKU BUNGA BI TERHADAP KURS RUPIAH DI INDONESIA PERIODE 2005-2014 - Tiara Nofia Landa; Tri Sukirno Putro; Wahyu Hamidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to investigate the effect of money supply, and BI rate on Exchange rate in Indonesia. This research uses secondary data in from of time series data that obtained from “Statistik Ekonomi Keuangan Indonesia”and “Badan Pusat Statistik” during the period of 2005 until 2014. An amperial analysis is carried out by using quantitive methode of multiple linear regression with 5% level of significant. The variable in this reserch are Indonesia Exchange Rate (as dependent variable), money supply and BI rate (as independent variables). The results show that money supply (M2) are significantly and positive impact on exchange rate . It can be seen from the value of the t statistic> t table is 4.655161 > 2.36462, with a probability value of 0.0023 <α (0.05). Mean while the BI Rate is significantly and positively impact on exchange rate. It can be seen from the value of the t statistic> t table is 3.167523 > 2.36462. with a probability value of 0.0158 <α (0.05). The finding in this research suggests money supply and BI Rate give dominant impact on exchange rate in indonesia. Goverment and related agencies, especially Bank Indonesia as policy maker must be carefully understood with those variables in order that they can control exchange rate variable and maintaining economic stability in order to avoid exchange rate fluctuation.Keywords : Money Supply, BI Rate and Exchange Rate